Phraseological interpretation of the different age stages of the human life cycle (on the material of the Czech language) - Volodymyrivna Kobyletska, Liudmyla (Slavia Centralis, 2022)
The article deals with the analysis of the phrase-semantic subgroup "age stages of the human life cycle", in terms of which phraseological units reflecting such age periods as "birth", "childhood", "adolescence", "adulthood", "old age", and "the end of human life" are studied in detail. The nucleus and peripheral constituents are defined and outlined of the given phrase-semantic subgroup. The nucleus constitutes PUs possessing in their semantic structure the maximum quantity of integral semes and expressing the semantic essence of the given phrase-semantic subgroup explicitly. The periphery zone is segmented into close, distant, and back peripheries. Particular attention is paid to the use and functioning of the studied PUs in the texts of the Czech National Corpus. The quantitative and qualitative characteristics are traced and analysed of innovative forms of PUs.
Keywords: phraseological unit (PU); semantics; nucleus; periphery; innovation